Sustainable event tourism: Case study city of Pula, Croatia - Jasmina Grzinic; Nikola Vojnovic (UTMS Journal of Economics, 2014)
Modern tourism expands through cultural experience, which is reflected in economic, ecological and socio-cultural effects on destinations. Event tourism is a growing market segment and represents a challenge for all destination stakeholders. As the largest town in the Croatian part of Istria, the City of Pula represents a valid basis for the development of event tourism due to its coastal geography and rich cultural and historical heritage from antique, medieval and new age periods. The festival and event organisers in Pula use historical and cultural themes in order to develop annual attractions by which they draw in tourists and brand the destination. In this paper, the hypothesis is set on the lack of benefits from event organisation in the destination (the City of Pula) in the ecological, economic and socio-cultural senses. In resolving of research problems with authorised representatives of local boards Arena, Monte Zaro and Stinjan, standardised, semi-structured and problem-centred interviews were conducted for the purposes of contribution to research relative to sustainability and responsibility of events in tourism.
Keywords: Q01; O44; L83; 330; City of Pula; sustainability; event tourism; environment; local community; economic effects